Concentrations, correlations and chemical species of PM2.5/PM10 based on published data in China: Potential implications for the revised particulate standard. (February 2016) - Zhou, Xuehua; Cao, Zhaoyu; Ma, Yujie; Wang, Linpeng; Wu, Ruidong; Wang, Wenxing
Abstract: Particulate matter (PM) has been of great concern in China due to the increasing haze pollution in recent years. In 2012, the Chinese national ambient air quality standard (NAAQS) was amended with a "more strict" regulation on the PM concentrations, i.e., 35 and 70 µg/m 3 for annual PM2.5 and PM10 averages, respectively (Grade-Ⅱ, GB3095-2012). To evaluate the potential of China to attain such new NAAQS and provide a more generalized chemical profile of PM in China, a comprehensive statistical analysis was carried out based on the published data of parallel PM2.5 and PM10 mass concentrations and chemical compositions of PM2.5 and PM10 . The results show that most of the measured concentrations far exceed the new NAAQS. PM2.5 and PM10 show a strong positive correlation (R 2  = 0.87, p < 0.01) with PM2.5 accounting for about 65% of PM10, suggesting that the abatement of PM2.5 is crucial for reducing PM pollution and hence improving air quality in China. Organic carbon (OC), sulfate and crustal species are the three major components of PM. The NO3 - /SO4 2- ratios are 0.43 ± 0.26 in PM2.5 and 0.56 ± 0.29 in PM10, and the OC/EC ratios are 3.63 ± 1.73 in PM2.5 and 4.17 ± 2.09 in PM10, signifying that the stationary emissions from coal combustion remain the main PM source. An evaluation of PM2.5 situation in current China was carried out and the results show that it would take about 27 years to meet the limit value of 35 µg/m 3 in the revised standard, implying a rigorous challenge in PM2.5 control in China in the future. Highlights: ∙ The characteristics of PM are obtained in China based on published observation data. ∙ PM2.5 and PM10 have a strong correlation with 65% PM2.5 in PM10 cross the nation. ∙ OC, sulfate and crustal species are the three most major components in PM in China. ∙ Stationary source emissions from coal combustion are still the main sources of PM. ∙ It is a serious challenge to reach PM2.5 standard in the future in China.